FROM THE HISTORY OF THE UZBEKISTAN JUDICIAL SYSTEM - Ikhtiyor Khudoikulov (Innovate Conferences, 2025)
The article discusses the life and creative legacy of Sadri Ziyo, one of the important figures in the history of the judicial system of Uzbekistan. After the overthrow of the Bukhara Emirate, Sadri Ziyo, who held various positions in the government of the BSSR, worked as deputy chairman of the Sharia Department and the Court of Endowments, and as an employee of the Ibn Sino Library. The article discusses, in particular, Sadri Ziyo's information about the judges and magistrates who worked in the Bukhara Emirate through his work "Diary", which is of great importance in understanding the history of the judicial system of Uzbekistan.
Keywords: Sadri Ziyo, Bukhara People's Soviet Republic, Sharia Department, Court of Endowments, Ibn Sino Library, history of the judicial system of Uzbekistan, Bukhara Emirate, history of judges and magistrates, scientific heritage, cultural heritage